KAMUS BALI INDONESIA DALAM UPACARA MAPANDES - Maya Dewi, Ni Nyoman Citta (Humanis; Volume 5. No. 2. November 2013, 2014)
Dictionary Bali Indonesia in Ceremony of Mapandes aim to to document Balinese words in the field of ceremony of mapandes. Expected later this research good for generation hereinafter to become information center about ceremony of mapandes as well as expected this research can be continued by next generation to be completed again, morely special again, this research aim to for the description of words in ceremony of mapandes and of description wprds which used in ceremony of mapandes. Used method that is data collecting method. Process data collecting with technique record and technique note. Data which have been collected later, then analysed with method analyse data that is with system of corpus, card - gathered to be card to be compiled by alfabetis, then given nymph in the form of word equivalent or clear boldness. Data which have been analysed, then presented with informal and formal method. Used theory that is structural theory, developed by Ferdinand de Saussure. Its views collected by Charles Bally and of Albert Sechehaye in book entitling published Cours de Lingusitique Generale in 1916. This theory used because each;every words formed of smallest process that is morpheme, then or word of lexeme, generation word, and there also which in the form of word aliance. Theory of Leksikologi and of leksikografi also very is supporting this research because science studying about lexicon or vocabulary leksikologi. While way of making dictionary discussed in theory of Leksikografi. From result of research, got words form which in the form of headword, generation word ( afiksasi, reduplikasi, kompositum), and phrase. Form which at most found that is elementary form / headword. Amount of found entri that is counted 534 entri.
Keywords: dictionary, mapandes,